Perananan Lembaga Otoritas Jasa Keuangan Dalam Mengawasi Sistem Keuangan Islam Di Indonesia - Erina Nuralifianti; Fitriyyatul Masruroh; Linda Wardaningrum; Agus Eko Sujianto (Universitas 45 Surabaya, 2023)
The financial system is a system where this is very important so that it has a principal value role in running the economy in life. The financial system can also be interpreted as an economic order that exists in a country that has an important role and carries out all activities regarding various financial services where this is carried out by the financial institutions themselves, which have the main task and role of channeling funds. However, with the increasingly complex situation of the global financial system, an institution is needed which has a duty and role to carry out an arrangement and carry out supervision. The presence of the Financial Services Authority institution in the financial system in Indonesia makes finance in Indonesia increasingly well-conditioned. This is in accordance with the objectives of the Financial Services Authority, which is to serve as a supervisory body for the running of the financial system in Indonesia. The role of the Financial Services Authority (OJK) in overseeing the financial system in Indonesia is implemented through the Role of the Financial Services Authority in Consumer Protection and Conducting Investigations and the Role of the Financial Services Authority in Regulation and Supervision of Technology-Based Financial Services. Thus, in developments in the financial sector in Indonesia, the presence of OJK is considered capable as an institution to carry out supervision which is expected to be able to bridge the gap to help launch several activities of financial service institutions.